2018
DOI: 10.1111/jonm.12719
|View full text |Cite
|
Sign up to set email alerts
|

Improving discharge planning using the re‐engineered discharge programme

Abstract: Those responsible for education initiatives must make understanding nurses' learning preferences a priority to improve the quality of bedside practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are now established hospital in the home and transitional programmes that allow early hospital discharge and prevent hospital admission are beneficial. [23][24][25][26] A systematic review of interventions to reduce early hospital readmissions concluded that interventions were complex with more recent ones less effective in their review from 2009 to 2013. 11 Singaporean-based RCT showed some positive results but again highlighted the issues facing clinicians with patients with multiple comorbidity and complex care needs.…”
Section: Discussionmentioning
confidence: 99%
“…There are now established hospital in the home and transitional programmes that allow early hospital discharge and prevent hospital admission are beneficial. [23][24][25][26] A systematic review of interventions to reduce early hospital readmissions concluded that interventions were complex with more recent ones less effective in their review from 2009 to 2013. 11 Singaporean-based RCT showed some positive results but again highlighted the issues facing clinicians with patients with multiple comorbidity and complex care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, we perhaps need to examine the issue in a different manner and focus on transitional care following discharge from hospital for this cohort of patients as a way to prevent/reduce hospital readmission. There are now established hospital in the home and transitional programmes that allow early hospital discharge and prevent hospital admission are beneficial [17,18,19,20]. A systematic review of interventions to reduce early hospital readmissions concluded that interventions were complex with more recent ones less effective in their review from 2009 to 2013 [8].…”
Section: Discussionmentioning
confidence: 99%
“…Adams et al (2014) validated the RED toolkit as effective in reducing readmissions. The National Quality Forum and the Institute for Healthcare Improvement evaluated the RED toolkit as adequate for safe discharge planning practice (Roberts et al, 2018).…”
Section: Instrumentmentioning
confidence: 99%